Magnetic resonance monitoring of superparamagnetic iron oxide (SPIO)-labeled stem cells transplanted into the inner ear. (June 2015) - Watada, Yukiko; Yamashita, Daisuke; Toyoda, Masashi; Tsuchiya, Kohei; Hida, Naoko; Tanimoto, Akihiro; Ogawa, Kaoru; Kanzaki, Sho; Umezawa, Akihiro
Highlights: We used 1.5 T MRI to monitor stem cells transplanted into the cochlea of guinea pigs. SPIO-labeled transplanted cells could be detected in MR images for 2 weeks. This novel method will be helpful for stem cell therapy in inner ear regeneration. Abstract: In the field of regenerative medicine, cell transplantation or cell-based therapies for inner ear defects are considered to be promising candidates for a therapeutic strategy. In this paper, we report on a study that examined the use of magnetic resonance imaging (MRI) to monitor stem cells transplanted into the cochlea labeled with superparamagnetic iron oxide (SPIO), a contrast agent commonly used with MRI. First, we demonstrated in vitro that stem cells efficiently took up SPIO particles. This was confirmed by Prussian blue staining and TEM. In MRI studies, T2 relaxation times of SPIO-labeled cells decreased in a dose-dependent manner. Next, we transplanted SPIO-labeled cells directly into the cochlea in vivo and then performed MRI 1 h, 2 weeks, and 4 weeks after transplantation. The images were evaluated objectively by measuring signal intensity (SI). SI within the ears receiving transplants was significantly lower ( P < 0.05) than that of control sides at the 1-h assessment. This novel method will be helpful for evaluating stem cell therapies, which represents a new strategy for inner ear regeneration. To the best of our knowledge, this study is the first to demonstrate that local transplantation of labeled stem cells into the inner ear can be visualized in vivo via MRI.